The aquaponic farmer : a complete guide to building and operating a commercial aquaponic system - Southern, Adrian, 1982-; King, Whelm, 1977- (Canadian Books Collection, 2017)
Aquaponic farming--raising fish and vegetables together commercially--is the most promising innovation for a sustainable, profitable, localized food system. Until now, systems have largely focused on warm-water fish such as tilapia. A lack of reliable information for raising fish and vegetables in the cool climates of North America and Europe has been a major stumbling block. The Aquaponic Farmer is the game changer. Built around a proven 120-foot greenhouse system operable by one person, the book distills vast experience and complete step-by- step guidance for starting and running a cold-water aquaponics business. Coverage includes: A primer on cold-water aquaponics; Pros and cons of different systems; Complete design and construction of a Deep Water Culture system; Recommended and optional equipment and tools; System management, standard operating procedures, and maintenance checklists; Maximizing fish and veg production; Strategies for successful sales and marketing of fish and plants. As the only comprehensive commercial cold-water resource, The Aquaponic Farmer is essential for farmers contemplating the aquaponics market, aquaponics gardeners looking to go commercial, and anyone focused on high quality food production.